WOMEN'S KNOWLEDGE ABOUT OBSTETRIC VIOLENCE IN THE PREGNANCY-PUERPERAL CYCLE (REMUNOM, 2025)
The medicalization of childbirth and the excessive use of unnecessary interventions are characterized as obstetric violence, a practice that contributes to increased maternal and infant mortality. This form of violence, committed by health professionals throughout the pregnancy-puerperal cycle, compromises women's autonomy and negatively impacts their health and that of their newborns. This study aimed to identify the knowledge of women treated by the Unified Health System (SUS) about obstetric violence and their rights during pregnancy, childbirth and the puerperium. This is an exploratory and descriptive study with a qualitative approach, conducted through structured interviews with pregnant women in the third trimester and postpartum women who use a basic health unit in the interior of Rio Grande do Sul. Among the eight women interviewed, the ages ranged from 21 to 32 years; the majority were white, single, and had completed high school or had incomplete higher education. Regarding occupation, a variety of roles were observed, including administrative, production, and service activities. Six women had one child and two had two; five reported a cesarean section, two reported a normal birth, and one had not given birth at the time of the interview. The main results showed that the professionals involved in assisting women during pregnancy and childbirth do not adopt conduct that helps reduce the occurrence of obstetric violence or guarantee their autonomy, which causes misinformation to persist. We conclude that the results contribute to understanding the perception of SUS users regarding obstetric violence and highlight the importance of health education and the guarantee of reproductive rights.